2020
DOI: 10.1002/adfm.202000526
|View full text |Cite
|
Sign up to set email alerts
|

High Thermoelectric Performance in Sulfide‐Type Argyrodites Compound Ag8Sn(S1−xSex)6 Enabled by Ultralow Lattice Thermal Conductivity and Extended Cubic Phase Regime

Abstract: Argyrodites with a general chemical formula of A 8 BC 6 are known for complex phase transitions, ultralow lattice thermal conductivity, and mixed electronic and ionic conduction. The coexistence of ionic conduction and promising thermoelectric performance have recently been reported in selenide and telluride argyrodites, but scarcely in sulfide argyrodites. Here, the thermoelectric properties of Ag 8 Sn(S 1−x Se x ) 6 are reported. Specifically, Ag 8 SnS 6 exhibits intrinsically ultralow lattice thermal conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…As a result, a peak figure of merit ZT ( ZT ∼ 1.5) is attained at 850 K. 34 Another similar compound Cu 8 GeSe 6 has a low κ L value of 0.2 W m −1 K −1 and ZT value as high as 1.0. 24 For the Ag 8 SnS 6 compound, it is reported that lattice part κ L is 0.31–0.61 W m −1 K −1 , 37 much higher than those observed in Ag 9 GaSe 6 and Cu 8 GeSe 6 and that the recorded ZT value is only 0.8. Therefore, it is highly likely to improve the TE performance of Ag 8 SnS 6 if its κ L value can be further reduced.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…As a result, a peak figure of merit ZT ( ZT ∼ 1.5) is attained at 850 K. 34 Another similar compound Cu 8 GeSe 6 has a low κ L value of 0.2 W m −1 K −1 and ZT value as high as 1.0. 24 For the Ag 8 SnS 6 compound, it is reported that lattice part κ L is 0.31–0.61 W m −1 K −1 , 37 much higher than those observed in Ag 9 GaSe 6 and Cu 8 GeSe 6 and that the recorded ZT value is only 0.8. Therefore, it is highly likely to improve the TE performance of Ag 8 SnS 6 if its κ L value can be further reduced.…”
Section: Introductionmentioning
confidence: 91%
“…The stronger the bonding is, the higher the sound velocity. 23,66 In this regard, there is a dual effect that regulates k L : one is point defects formed by cation substitution, which reduces the lattice part k L , 37 and the other is the introduction of stronger Cu-Se bond than Ag-Se, which increases the k L value. That is why we observed the minimum k L $ 0.12 W K À1 m À1 at x ¼ 0.05 and 645 K.…”
Section: Transport Properties and Te Performancementioning
confidence: 99%
“…Similar feature has been also observed in other superionic compounds such as Cu 2‐ δ (S, Se, Te) [ 28–31 ] and argyrodites. [ 32 ]…”
Section: Figurementioning
confidence: 99%
“…In addition, it is also quite crucial to seek potential materials with intrinsically low κ L , such as liquid‐like materials [ 18 ] and low‐sound‐velocity materials. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is also quite crucial to seek potential materials with intrinsically low κ L , such as liquid-like materials [18] and low-sound-velocity materials. [19] In the past decade, materials with layered structures, such as SnSe, [20][21][22][23][24] In 4 Se 3 , [25] and SnS, [26,27] have sparked significant research owing to their excellent TE performance. Their layered structure and strong lattice anharmonicity naturally lead to ultralow κ L .…”
Section: Introductionmentioning
confidence: 99%